2019
DOI: 10.15244/pjoes/89544
|View full text |Cite
|
Sign up to set email alerts
|

Applying Bio-Slow Sand Filtration for Water Treatment

Abstract: Water-borne typhus, dysentery, viral hepatitis, diarrhoea, and other intestinal infectious diseases are the prevailing diseases in the rural areas in China. The harvested rainwater is easily contaminated by air pollution, surface runoff fertilizer and pesticides, solid waste and chips at the rainwater-harvesting surface (rubbish, animal faeces, etc.), and anthropogenic pollution. With the development of technology, products made of ceramic filters have been widely used in cities where tapwater is available. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
(12 reference statements)
1
5
0
2
Order By: Relevance
“…Expectedly, the efficiency of both filters considered moderate which partly agree with findings of similar study [50]. As a matter of fact the removal of heavy metals is commonly below 80% [51] and HSSF is not recommended for removal of industrial chemicals such as Zn, Cr,…etc., rather it is best for removal of pathogenic microorganisms [19]. Hierarchical Cluster Analysis (HCA) Dendrogram (Fig.…”
Section: Chemical Characteristicssupporting
confidence: 87%
“…Expectedly, the efficiency of both filters considered moderate which partly agree with findings of similar study [50]. As a matter of fact the removal of heavy metals is commonly below 80% [51] and HSSF is not recommended for removal of industrial chemicals such as Zn, Cr,…etc., rather it is best for removal of pathogenic microorganisms [19]. Hierarchical Cluster Analysis (HCA) Dendrogram (Fig.…”
Section: Chemical Characteristicssupporting
confidence: 87%
“…In the BSF case, specific conditions as the maintenance of bacteria community may be an indication of bacteria selectivity after consecutive backwashing, which could also lead to a faster ripening, favouring the removal of target contaminants (Flemming et al, 2016;Ikhlef and Basu, 2017). Other studies have reported the importance of bacterial degradation on SSF for removal of target contaminants such as organic compounds and nutrients, and the selectivity of specific bacteria due to these contaminants over operational time or treatment process (Aslan and Cakici, 2007;D'Alessio et al, 2015;Li et al, 2018Li et al, , 2017Liu et al, 2019;Miltner et al, 1995;Summers, 2014;Zearley and Summers, 2012).…”
Section: Biomass Considerations Regarding Bsf Operationmentioning
confidence: 99%
“…Proses biologis lebih optimal pada SSF, didukung kecepatan aliran lebih lambat (< 0,5 m/jam) dan waktu filtrasi lebih lama (1-6 bulan) sehingga aktivitas biologis lebih optimal [26] . Penyisihan utama SSF dengan lapisan schmutzdecke yang terdiri dari mikroorganisme hidup atau mati berupa bakteri, alga dan protozoa [27]. Aktivitas biologis mengurai senyawa organik dan partikel inert tersuspensi disaring secara fisik.…”
Section: ) Proses Biologisunclassified